Pengaruh Budaya Organisasi, Audit Internal, dan Pengendalian Internal terhadap Penerapan GCG - Aria, Dimas Fajar; Pahala, Indra; Khairunnisa, Hera (LPPM Universitas Negeri Jakarta, 2023)
This study aims to analyze the influence of organizational culture, internal audit and internal control on the implementation of good coprorate governance (GCG). This study used primary data in the form of questionnaire data obtained from the Perusahaan Umum Pengangkutan Penumpang Djakarta. The data collection technique is the technique of distributing questionnaires which are distributed to the research sample locations. The purposive sampling technique was used as a sampling technique with employees who were at employee grades 1-18 from the research sample. The analytical method used in this study used multiple linear regression analysis using the Statistical Program for Social Science (SPSS) 25 software. The results showed that organizational culture has a positive effect on GCG, internal audit has a positive effect on GCG and internal control has a positive effect on GCG. negative towards GCG.